Management of the Behaviour of the Company’s Personnel Based on Corporate Culture - Zhao, Jing; Brychko, Alina (Dr. Viktor Koval, 2023)
Introduction. A high degree of integration of management activities with information systems enables the use of corporate culture’s potential. Due to the multifactorial nature of external and internal influences and the significant dynamics of changes in factors to increase the effectiveness of managing the behavior of the company's personnel based on corporate culture, management needs specialized information systems for support and decision-making. The effectiveness of the implementation of such systems largely depends on their mathematical core and the efforts of management to adapt the staff to the conscious use of all the opportunities provided by information technologies by the staff. Aim and tasks. The aim of the study is to develop a mathematical model of personnel management behavior based on corporate culture and the stratification of personnel by local groups for the subsequent stratification of assessment factors and management tools. Results. A mathematical model of personnel behavior management based on corporate culture has been developed to stratify personnel by local groups and, on this basis, stratification of evaluation factors and tools for managing the behavior of these groups of employees was carried out. The results of the mathematical model implementation were stratified. Factors that contribute to the effectiveness of managing the behavior of a company's personnel were identified. Informal methods and tools for moral motivation have also been identified. This indicates that a sudden decrease in the level of interactive communication among personnel might be a sign of their passive resistance to management actions. The fragmentation of the level of interactive communication by local teams is proposed as an indicator of a decrease in the effectiveness of managing the behavior of personnel in interdisciplinary teams. Conclusions. The developed mathematical model avoids management decisions that contradict the principles of corporate culture, resulting in a negative result from their implementation. The mathematical formalization of management decisions will contribute to the awareness of these decisions by the team as objective decisions, and can be used for the moral motivation of the staff. This allows employees to specify themselves as members of a single team and evaluate their career opportunities in a relevant manner.